THE DETERMINANTS OF RURAL POVERTY (A Study of Tobacco Farmers in Temanggung) - Fuad Hasyim (Global Review of Islamic Economics and Business, 2018)
Rural poverty is a problem that seemed vicious because poverty is a structural problem that will always be there. Poverty of farmers in rural areas must be addressed in an effort to increase the capacity and capability of farmers to form farmers' productive behaviors that have an impact on increasing empowerment.This study tried to explore the problems of poverty in rural areas, particularly poverty tobacco farmers in Temanggung. This is motivated because the Temanggung tobaccos are the world's best tobacco, but its majority people are poor. This study uses primary data approach, the method of Structural Equation Modeling (SEM) using path analysis. Then in-depth explanation with interviews and observations analysis techniques to obtain optimal qualitative interpretation.The results showed that the capacity, culture, government empowerment, social capital and religiosity as independent variables affect the attitudes of society, which in turn affect the empowerment of the poor as poverty reduction efforts.